Application of socio-ecological model in developing preventive strategies against suicidal ideation and suicidal attempt among youth in low and middle-income countries: a scoping review - Zulkiply, Siti Hafizah; Abdul Manaf, Rosliza (Malaysian Medical Association, 2022)
Introduction: Suicide is recognized as an important public health concern, as it is the second leading cause of death among young people. About 80% of all suicide cases occur in low- and middle-income countries (LMICs). Understanding the risk factors for suicidal behaviours among young people in LMIC is important in developing preventive strategies; however, evidence on this is still lacking. Socio-ecological model (SEM) is a suitable framework in explaining the factors of suicidal behaviour. The aim of this review is to identify the factors associated with suicidal ideation and suicidal attempt among young people in LMIC, guided by the SEM model, and eventually develop its preventive strategies. Materials and methods: This review has two parts. The first part is a scoping review of the factors associated with suicidal ideation and attempt among young people. The search was conducted in Pubmed, Scopus, and PsycInfo. The second part is the development of preventive strategies according to the identified factors. Both parts will be guided by the SEM model. Results: A total of ten studies with 45,278 participants that matched the criteria are included in this review. The review found that the risk factors for suicidal ideation among young people in LMIC are being female, psychiatric illness, psychology problem, smoking, alcohol intake, victim of abuse, bullied, and food insecurity. The preventive strategies include policy, mental healthcare services, awareness programme, and coping strategies. Conclusion: More epidemiological studies are needed to evaluate the risk factors of suicide that are unique in LMIC, such as help-seeking behaviour and available mental healthcare services. Suicide prevention requires concerted effort of policymakers, healthcare services, community and individual; thus, SEM framework is suitable as a guidance for suicide prevention.